X-ray-facilitated redox cycling of nanozyme possessing peroxidase-mimicking activity for reactive oxygen species-enhanced cancer therapy. (September 2021) - Zhang, Chenyang; Wang, Xin; Dong, Xinghua; Mei, Linqiang; Wu, Xiaochen; Gu, Zhanjun; Zhao, Yuliang
Abstract: Nanomaterials with shifting or mixed redox states is one of the most common studied nanozyme with peroxidase-like activity for chemodynamic therapy (CDT), which can decompose hydrogen peroxide (H2 O2 ) of tumor microenvironment into highly toxic reactive oxygen species (ROS) by a nano-catalytic way. However, most of them exhibit an insufficient catalytic efficiency due to their dependence on catalytic condition. Herein, a potential methodology is proposed to enhance their enzymatic activity by accelerating the redox cycling of these nanomaterials with shifting or mixed redox states in the presence of X-ray. In this study, the nanocomposite consisting of SnS2 nanoplates and Fe3 O4 quantum dots with shifting or mixed redox states (Fe 2+ /Fe 3+ ) is used to explore the strategy. Under external X-ray irradiation, SnS2 cofactor as electron donor can be triggered to transfer electrons to Fe3 O4, which promotes the regeneration of Fe 2+ sites on the surface of the Fe3 O4 . Consequently, the regenerated Fe 2+ sites react with the overexpressed H2 O2 to persistently generate ROS for enhanced tumor therapy. The designed nanocomposite displays the synergistic effects of radiotherapy and CDT. The strategy provides a new avenue for the development of artificial nanozymes with shifting or mixed redox states in precise cancer treatments based on X-ray-enhanced enzymatic efficacy.